Inside the Pakistan Army : a woman's experience on the frontline of the war on terror - Schofield, Carey (London : Biteback Pub., 2011)
"The Pakistan Army is at the forefront of the West's war on terror, policing the border with Afghanistan and the lawless tribal agencies where Osama bin Laden is said to be hiding. Since October 2009 more than 30,000 troops have been mounting a huge offensive to crush the insurgents of the Taliban. More recently, hundreds have died in suicide attacks across the country as the Islamists have brought their war against the pro-Western Government to the country's cities. The success or failure of the Pakistan Army in this and similar offensives is now seen as critical to the West's hopes of halting the spread of Islamist extremism outside of what the Americans call AfPak, the theatre of operations which is occupying Britain, the US and their allies. If the Pakistan Army fails to stamp out the Taliban insurgency, it could become unstoppable, with the drastic spread of global terrorism. The army itself is full of apparent contradictions. Its officers may have the clipped voices and moustaches of their British predecessors but they are not immune to the anti-Western passions prevalent in Pakistan. So are they reliable allies in the war on terror? No other writer--Pakistani or foreign--can answer this critical question more clearly than Schofield. No other writer knows these men better. For five years, Carey Schofield travelled everywhere with them, so close they even had a uniform made for her. Inside the Pakistan Army is the truth about all of these men and their vital role in the war on terror."--Publisher's description.
The question of the Pakistan Army -- The place of the Army in Pakistan -- How the Pakistan Army got to be where it is today -- Fauji life -- Inside the ISI -- General Musharraf -- Tackling the militants -- The war goes on -- The death of Faisal Alavi -- Conclusion -- Appendix 1: Operation Nepal and the men of steel -- Appendix 2: Armoured regiments of the Pakistan Army -- Appendix 3: Pakistan Army Corps.
Includes index.
Keywords: Pakistan. -- Army; War on Terrorism, 2001-2009.; Pakistan -- Armed Forces